2021
DOI: 10.1007/s00127-021-02215-5
|View full text |Cite
|
Sign up to set email alerts
|

Trends in inpatient care for psychiatric disorders in NHS hospitals across England, 1998/99–2019/20: an observational time series analysis

Abstract: Purpose It is unclear how hospitals are responding to the mental health needs of the population in England, against a backdrop of diminishing resources. We aimed to document patterns in hospital activity by psychiatric disorder and how these have changed over the last 22 years. Methods In this observational time series analysis, we used routinely collected data on all NHS hospitals in England from 1998/99 to 2019/20. Trends in hospital admissions and bed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“…Length of hospitalization did not show a significant change with time, which is inconsistent with previous reports ( 12 , 16 , 20 ); previous studies pointed out that the hospitalization duration was shortened because of the use of long-acting formulations of atypical antipsychotics, which are also currently widely used in our center; however, long-acting formulations are not widely prescribed to pediatric patients. The application of long-acting injections for the treatment of SCZ was recommended in the 2015 Chinese expert consensus report ( 21 ); however, a study conducted in 2020 on the application pattern of long-acting injections in SCZ in Asia reported that the application rate of long-acting injections in China is still low, at about 0.66% ( 22 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Length of hospitalization did not show a significant change with time, which is inconsistent with previous reports ( 12 , 16 , 20 ); previous studies pointed out that the hospitalization duration was shortened because of the use of long-acting formulations of atypical antipsychotics, which are also currently widely used in our center; however, long-acting formulations are not widely prescribed to pediatric patients. The application of long-acting injections for the treatment of SCZ was recommended in the 2015 Chinese expert consensus report ( 21 ); however, a study conducted in 2020 on the application pattern of long-acting injections in SCZ in Asia reported that the application rate of long-acting injections in China is still low, at about 0.66% ( 22 ).…”
Section: Discussioncontrasting
confidence: 99%
“…This trend was reported in many studies that were not age-restricted ( 13 – 15 ). However, in a UK study ( 16 ), it was noted that only the prevalence rates of anxiety and eating disorders increased and those of all other psychiatric disorders decreased in the unrestricted age context. However, for children and adolescents, hospitalization for DD continued to increase by 5.6% between 1998 and 2019.…”
Section: Discussionmentioning
confidence: 97%
“…The increasing demand for inpatient admissions 11 may indicate that ACEDS are unable to deliver timely evidence-based therapies to prevent patients from deteriorating severely. NHSE Digital 12 reported a fourfold rise in hospital admissions with primary or secondary eating disorder diagnoses between 2007/8 and 2020/21 (~70% are adults).…”
Section: Demand: Annual Referral Patternsmentioning
confidence: 99%
“… 13–15 For instance, in England hospital admissions for EDs doubled between 1998 and 2020 while admissions for other severe mental disorders decreased. 16 This situation appears to have been further exacerbated by the ongoing COVID-19 pandemic. Internationally, research has indicated a rise in new ED presentations, increases in symptom severity and high levels of deterioration, relapse and comorbidities in those with established EDs.…”
Section: Introductionmentioning
confidence: 99%